2016
DOI: 10.1590/s1517-707620160002.0045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characteristics of groundnut shell particle reinforced polylactide nano fibre

Abstract: The PLA-groundnut shell solution is electrospun to produce nanocomposite fibre. The spinneret containing the composite solution was placed 24.7 cm away from the aluminium collector, tilted at an angle of 30 °, and the solution flow rate kept at 1 mL/min. Groundnut Shell particle (GSP) weight fraction used was varied from 3 -8 wt. %. Particle reinforced nanofibres were formed on the collector from the composite solution at 26 kV. These nanofibres were subjected to tensile test and the result indicates that at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
1
13
1
Order By: Relevance
“…Chen and Liu (2008) also obtained lower tensile strength at the same filler weight fraction using cellulose nanocrystals soybean protein fibre. Results obtained from this study are found superior to our earlier report on palm fruit bunch and groundnut shell filled electrospun fibres (Adeosun, Akpan, Gbenebor, Peter, & Olaleye, 2016b;Adeosun, Taiwo, et al, 2016c). This improved result is attributed to the effect of reinforcement particles on the fibres and the structural stability imparted through synergy between process and material parameters.…”
Section: Effects Of Processing Parameters On Tensile Properties Of Elcontrasting
confidence: 84%
See 1 more Smart Citation
“…Chen and Liu (2008) also obtained lower tensile strength at the same filler weight fraction using cellulose nanocrystals soybean protein fibre. Results obtained from this study are found superior to our earlier report on palm fruit bunch and groundnut shell filled electrospun fibres (Adeosun, Akpan, Gbenebor, Peter, & Olaleye, 2016b;Adeosun, Taiwo, et al, 2016c). This improved result is attributed to the effect of reinforcement particles on the fibres and the structural stability imparted through synergy between process and material parameters.…”
Section: Effects Of Processing Parameters On Tensile Properties Of Elcontrasting
confidence: 84%
“…In our earlier studies it was shown that controlling the solution concentration leads to control of the fibre diameter and surface morphology (Adeosun, Akpan, Gbenebor, Peter, & Olaleye, 2016a). In another study, it was also shown that addition of particles can lead to the formation of porous fibre network structure (Adeosun, Akpan, Gbenebor, Peter, & Olaleye, 2016b;Adeosun, Taiwo, et al, 2016c). These porous materials are capable of absorbing water and other solvents making them a potential for application in drug delivery applications (Adeosun, Akpan, Gbenebor, Peter, & Olaleye, 2016b).…”
Section: Introductionmentioning
confidence: 98%
“…In keeping with an earlier report by Adeosun et al . 16 , the nanocomposite with 3 phr showed better filler distribution and hence better crystalinity and cross-links; resulting in improved modulus. This is evident at different percent elongation reported in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…2b). The poor strength exhibited by unreinforced PLA could be attributed to poor interfacial bonding caused by the presence of non-cellulose and impurity [33]. The Elastic modulus of scaffolds revealed that incorporating 0.75 g Ag + S and 0.05% w/w A. linearis (EF2) to PLA solution culminated in a nanofiber with the superlative stiffness of 2.11 GPa, highest compared to all fabricated nanofibers (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The addition of 1 g Ag + S collagen and 0.025% w/w AL (EF 1) improved PLA's ductility to a maximum magnitude of 39.8%, hence showing that reinforcements had improved interfacial adhesion at the matrix interface. This restricts easy glide of the filler particles over the matrix giving rise to higher ductility [33]. Fig.…”
Section: Mechanical Characterizationmentioning
confidence: 99%